Medieval Disability Sourcebook Western Europe - McNabb, Cameron Hunt (punctum books, 2020)
The field of disability studies significantly contributes to contemporary discussions of the marginalization of and social justice for individuals with disabilities. However, what of disability in the past? The Medieval Disability Sourcebook: Western Europe explores what medieval texts have to say about disability, both in their own time and for the present.This interdisciplinary volume on medieval Europe combines historical records, medical texts, and religious accounts of saints' lives and miracles, as well as poetry, prose, drama, and manuscript images to demonstrate the varied and complicated attitudes medieval societies had about disability. Far from recording any monolithic understanding of disability in the Middle Ages, these contributions present a striking range of voices-to, from, and about those with disabilities-and such diversity only confirms how disability permeated (and permeates) every aspect of life.The Medieval Disability Sourcebook is designed for use inside the undergraduate or graduate classroom or by scholars interested in learning more about medieval Europe as it intersects with the field of disability studies. Most texts are presented in modern English, though some are preserved in Middle English and many are given in side-by-side translations for greater study. Each entry is prefaced with an academic introduction to disability within the text as well as a bibliography for further study. This sourcebook is the first in a proposed series focusing on disability in a wide range of premodern cultures, histories, and geographies.